2015
DOI: 10.1007/s00586-015-3944-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel posterior technique to temporize life-threatening hemorrhage after great vessel laceration during posterior osteotomy

Abstract: The posterior peri-vertebral approach can potentially be used by a spine surgeon during a life-threatening situation to temporarily occlude great vessel hemorrhage while waiting for the assistance of a vascular/trauma team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…No matter what kind of osteotomies 12,13,14 , these procedures generally improve kyphotic deformity by shortening the posterior column and lengthening the anterior column. Ji et al 12 found that aortic length increased by 2.2 cm averagely after closing-opening wedge osteotomy and the amount of aortic lengthening correlated positively with the degree of kyphosis correction, indicating that the aorta was more vulnerable to get injured in correction of more severe kyphotic deformities.…”
Section: Discussionmentioning
confidence: 99%
“…No matter what kind of osteotomies 12,13,14 , these procedures generally improve kyphotic deformity by shortening the posterior column and lengthening the anterior column. Ji et al 12 found that aortic length increased by 2.2 cm averagely after closing-opening wedge osteotomy and the amount of aortic lengthening correlated positively with the degree of kyphosis correction, indicating that the aorta was more vulnerable to get injured in correction of more severe kyphotic deformities.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Although the vascular complication is rare, the consequence may be quite devastating [ 13 16 ].…”
Section: Discussionmentioning
confidence: 99%